Konstruksi Makna Fitur Tiktok Repost Sebagai Media Ekspresi Diri pada Generasi Z - Utami, Sabrina Rahma; Fahira, Aldine Ginandra; Ritonga, Rajab; Dunan, Amri (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the construction of meaning of the TikTok Repost feature as a medium for self-expression and understand its role in shaping Generation Z's communication practices and digital identity. This study uses a qualitative approach with a constructivist paradigm. Research data were obtained through observation, in-depth interviews, and documentation of six Generation Z informants who actively use the TikTok Repost feature and five validators. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions to find patterns of meaning from the informants' experiences. The results show that the TikTok Repost feature is interpreted as a symbolic communication space that allows Generation Z to express feelings, show personal preferences, and build a digital self-representation. Through the selection and re-dissemination of content, users not only share information but also construct identities based on personal values, interests, and experiences. Furthermore, the Repost feature acts as a safe space for indirect self-disclosure and builds interactions with audiences through digital responses such as likes, messages, and reposts. These findings indicate that TikTok Repost is not just a content-sharing feature, but a digital communication practice that allows Generation Z to manage, display, and negotiate their identities in the social media environment.